Effect of particle content on microstructure and deformation mechanism of in-situ Al2O3p/Al0.25CoCrFeNi high entropy alloy matrix composites - Tuo Xu; Wenchen Zhuang; Suhui Meng; Zheng Ma; Li Jiang; Tongmin Wang; Zhiqiang Cao (Journal of Materials Research and Technology)
The strength-ductility trade-off is a common dilemma in the field of high entropy alloys (HEAs). Incorporating reinforcement particles into HEAs to form HEA matrix composites (HEAMCs) has become an effective method to alleviate this problem. In this work, the in-situ nano (Al2O3p)x/Al0.25CoCrFeNi (x = 0.3–6.0 vol%) composites were prepared by vacuum arc melting, followed by cold rolling and annealing. The effects of particulate content on the microstructures and mechanical properties of the new HEAMCs were investigated. It is found that the Al2O3p/Al0.25CoCrFeNi composites consist of a face-centered cubic (FCC) phase with nano Al2O3 particles embedded. When the particulate content is lower than 0.9 vol%, the Al2O3 particles are uniformly distributed without obvious agglomeration and exhibit spherical or polygonal shapes with sizes below 100 nm. The 0.8 vol% Al2O3 HEAMC exhibits the best mechanical properties with tensile yield strength (YS), ultimate tensile strength (UTS) and elongation (EL) of 346 MPa, 629 MPa and 58.0 %, respectively, increased by 18.1 %, 5.4 % and 3.9 %, compared to Al0.25CoCrFeNi HEA. The simultaneous improvement of strength and plasticity in the 0.8 vol% Al2O3 HEAMC can be attributed to the activation of 2nd twin by the particle-induced strengthening effect, resulting in a higher twin density in the HEAMC.